PARADIGMA KAUM PURITAN DALAM PEMBENTUKAN KEYAKINAN BERAGAMA INTERN SEKTE/MAZHAB BUDDHA DI INDONESIA - Warsito Warsito (Jurnal Ilmiah Kampus: Sati Sampajanna, 2019)
The emergence of puritan religious groups with a strong character, it will be forced to reexplorethe relationship between religion and pluralism. The group will remain ignorant of itsdoctrines and opinions and assume that with this belief they will claim the most correct. Puritangroups have variations in names and movements but their diversity of character has the same lines andcorridors. Puritan groups in Buddhism arise in large sects or sects in Indonesia such as the puritangroups of the Indonesian Theravada Buddhist Council, Maitreya groups, Mahayana groups, Tridharma Indonesia, and others.In this study using a qualitative approach (quality research) which reveals a phenomenon togain understanding with data in the form of qualitative data. This research is to find out the paradigmof Buddhist puritans in a plural society that is by openly interviewing schools of Buddhism. Inqualitative research the source of data comes directly from what is experienced by researchers as themain instrument, data embodied in words or images, pay more attention to process rather than results,in analyzing data more likely to use inductive methods.The results obtained show that there are different paradigms in Buddhism regarding theemergence of puritans. The different paradigm followed by listening to responses from religious leadersand youth in the school of Buddhism. After writing in this research, hopefully it will benefit to youngpeople, religious leaders, Buddhist communities and other communities in general.